Estimation of resultant airframe forces for a variable pitch fan operating in reverse thrust mode - Rajendran, David John; Tunstall, Richard; Pachidis, Vassilios (American Society of Mechanical Engineers (ASME), 2022)
The resultant forces with a reverse thrust Variable Pitch Fan (VPF) during the aircraft landing run are computed from the installed reverse thrust flow field obtained from an airframe-engine-VPF research model. The research model features a reverse flow capable VPF design in a future, geared, high-bypass ratio 40000 lbf engine as installed onto a twin-engine airframe in landing configuration, complete with a rolling ground plane to mimic the runway. The reverse thrust flow field during the aircraft landing run is obtained from 3D RANS/URANS solutions of the model. The evolution of the installed dynamic reverse thrust flow field is characterized by the interaction of the VPF induced reverse flow with the free stream. Several flow features like reverse flow wash-down by the freestream, external swirling helical flow development, pylon flow obstruction, 180° flow turn into the engine, subsequent separated flows, wake interactions and multi-pass recirculating flows are observed. The resultant airframe forces due to the reverse thrust flow field is estimated by adaptations of momentum based far-field and near-field methods. In the active thrust reverser engagement regime of 140 to 40 knots, the VPF generates a sufficient axial airframe decelerating force in the range of 45% to 8% of maximum take-off thrust. A drag decomposition study and a notional ‘blocked-fan’ analysis are described to understand the stack-up of the axial decelerating force. Additionally, the resultant force has a landing speed dependent lateral force component because of the pylon obstruction induced flow non-uniformity. A beneficial downforce component due to upward deflection of streamlines is also observed. The quantification of the resultant forces from the baseline installed airframe-engine-VPF reverse thrust flow field is a necessary step to explore the feasibility of the VPF reverse thrust system for future efficient turbofan architectures, understand force generation mechanisms and to identify areas for subsequent design improvement.
Keywords: variable pitch fan; reverse thrust; feasibility study; installed flow field; far field and near field methods